A Study of Customer Delight with Special Reference to HDFC Bank In Delhi And NCR Region (International Journal of Scientific Research and Management (IJSRM), 2017)
Today businesses have begun to realize that simply satisfying customers may not be enough, rather they should strive for Customer Delight. Creating a customer for life, requires companies to take their customers to the next level (i.e. Customer Delight) from satisfaction to delight state. Companies need to elevate the relationship from casual to a more intimate relationship of loyalty. The present research aims to identify the factors of Customer Delight in HDFC bank and to study the association of demographic variables on the various identified factors that cause Customer Delight in HDFC Bank in Delhi and NCR using non-probability convenience sampling. The collected data was analysed by using correlation and multiple regression to trace the factors that motivated customers to remain with the bank or make them delighted and to further study the association of demographic variables on factors affecting Customer Delight Chi-square test was used. The key findings of the study were that the most important factors which help to build the Customer Delight in HDFC Bank are the Tangibles and Assurance offered by the Bank. In contrast, customers felt least delighted with the price of the services in which the bank charges certain amount on account maintenance. The main limitation of this study is that it has not been able to cover consumers belonging to the rural/ semi urban branch of HDFC Bank and hence may not be a true reflection of all the customers of HDFC Bank.